2014
DOI: 10.5606/kbbihtisas.2014.48108
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with persistent allergic rhinitis treated with desloratadine monotherapy or desloratadine plus montelucast combination

Abstract: Objectives: This study aims to compare the effectiveness of desloratadine monotherapy and desloratadine plus montelukast combination therapy on quality of life in patients with persistent allergic rhinitis. Patients and Methods:This study consists of 40 patients (28 females, 12 males, mean age 29.8 years; range 17 to 44 years) referred to ear, nose, and throat outpatient clinic between May 2010 and September 2010. A six-week randomized, doubleblind, cross-sectional study was performed in two arms: In group 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…11,[13][14][15] At the end, 14 studies (15 articles) were included. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Characteristics of the included studies are shown in Table 1. A flow chart of the study retrieval and selection is presented in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…11,[13][14][15] At the end, 14 studies (15 articles) were included. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Characteristics of the included studies are shown in Table 1. A flow chart of the study retrieval and selection is presented in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Eight RCTs studied patients with seasonal AR (SAR) 12,16,19,21,22,24,25 and 6 RCTs studied perennial AR (PAR). 11,17,18,20,23 Four RCTs studied patients with persistent AR. 11,17,20 Two trials included patients with AR and comorbid asthma.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…For patients who do not tolerate INCSs or prefer not to use them, adding a leukotriene receptor antagonist to an oral or topical AH may be considered. 42,43 Responsive patients should be instructed to continue therapy during periods of allergen exposure. Those non-responsive to therapy (e.g., symptomatic after 4 weeks) should be stepped up.…”
Section: Management In Primary Care—treatmentmentioning
confidence: 99%